2022
DOI: 10.9745/ghsp-d-21-00316
|View full text |Cite
|
Sign up to set email alerts
|

The Equity Tool for Valuing Global Health Partnerships

Abstract: The Equity Tool (EQT) offers a practical guide for considering equity in 4 domains of practice: governance and process, procedures and operations, progress and impacts, and power and inclusion.The EQT is equity focused, user friendly, and can support reflective dialogue at any stage of the partnership, by individuals at any level in the partnership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…While not explicitly raised by the FGD participants, much of the discussion was based on the role of international NGOs and Australian based organisation on supporting health security the Pacific. A colonial history in the Region means that systems of dominance and power are deeply ingrained into the systems within which we work today, and, realistically, any effort for collaboration needs to take measures to counter the impact of such systems [47,48]. For example, one barrier to establishing effective working partnerships between Australia and countries in the Region is that such partnerships can create power differentials that mirror colonial relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While not explicitly raised by the FGD participants, much of the discussion was based on the role of international NGOs and Australian based organisation on supporting health security the Pacific. A colonial history in the Region means that systems of dominance and power are deeply ingrained into the systems within which we work today, and, realistically, any effort for collaboration needs to take measures to counter the impact of such systems [47,48]. For example, one barrier to establishing effective working partnerships between Australia and countries in the Region is that such partnerships can create power differentials that mirror colonial relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a comprehensive and pragmatic Equity Focused Tool for Valuing Global Health Partnerships was published and holds potential for supporting open dialogue in these partnerships. The tool is structured as a simple traffic light rating across key criteria in four domains (Governance & Process; Procedures & Operations; Progress & Impacts; and Power & Inclusion) and is designed to prompt reflective dialogue among all parties within the partnership [48].…”
Section: Discussionmentioning
confidence: 99%
“…, 2012 ) in understanding and operationalizing concepts of equity, human rights, gender equality and such similar concepts that are critical to embedding equity in research. We have included a large number of references for this domain ( Global Affairs Canada, 2015 ; Castillo and Harris, 2021 ; Porroche-Escudero and Popay, 2021 ; Larson et al , 2022 ) as we have found that it is the starting point for a broader equity-orientation process that researchers, teams and institutions may wish to pursue. A number of self-reflection tools and examples of application listed in Table 1 for this domain are intended to guide reflection on equity orientation and integration in research and research partnerships and place particular emphasis on capacity needs.…”
Section: The Eight Domains Of 8quitymentioning
confidence: 99%
“…, 2021 ; Porroche-Escudero et al. , 2021 ; Pratt, 2021a ; Larson et al , 2022 ; Public Health Agency of Canada, 2022 ). Specific ethical considerations exist for guiding the conduct of health systems and policy research and biomedical research such as ‘equity-relevant trials’ ( Mbuagbaw et al.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is critical to ensure the collection of gender-differentiated and equity data within global health research processes, programmatic implementation, and partnerships such as grantee selection, team and partnership structure (i.e., division of labour and decisionmaking) [52]. There has been a proliferation of proposed gender equality tools [64], equity principles and tools for partnerships [65,66] and empowerment-related indicators [67,68], including the Canadian-developed GENDER Index [69], but data collection methods and conceptual shortfalls have substantially limited their use. Collecting and reporting of data on equal partnerships is one way to monitor SDG progress [70], and these data should be publicly reported for accountability purposes and ongoing learning.…”
Section: Collect and Report On Gendered Data In Canadian Global Healt...mentioning
confidence: 99%